PERAN BANK SENTRAL DALAM MENCEGAH DAN MENGATASI KRISIS KEUANGAN DI INDONESIA - Mistar, Eristiana Choirun Nisa; Andreas Gede Pangestu; Rini Puji Astuti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Financial crises pose a significant challenge to a country's economic stability, leading to high inflation, currency instability, and reduced public confidence in the financial system. Central banks play a strategic role in maintaining financial stability through monetary policy, banking regulations, and coordination with the government and financial institutions. This study aims to analyze how central banks prevent and address financial crises and the strategies that can be implemented to strengthen the financial system against economic shocks. This research employs a qualitative approach through literature review by analyzing various scholarly journals, policy reports, and case studies from different countries. The findings indicate that the success of central banks in managing crises depends on the effectiveness of monetary policy, banking system preparedness, and synergy between fiscal and monetary policies. Additionally, emerging challenges such as financial digitalization and global market volatility require more adaptive supervisory strategies. In conclusion, central banks must continuously innovate their financial stability policies by strengthening regulations, enhancing transparency, and adopting digital technologies to mitigate future risks.